2012
DOI: 10.1149/1.3700891
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Random Telegraph Signal with PD SOI MOSFETs

Abstract: A novel method, called random telegraphy signal (RTS), was constructed to characterize the gate oxide quality and reliability of metal-oxide-semiconductor field-effect-transistors (MOSFETs). With the aggressive scaling of device size, drain current RTS (I D -RTS) become a critical role in carrier transport of MOSFETs. Besides, RTS in gate leakage current (I G -RTS) was denoted as the other new method to understand property of gate oxide. Recently, the study of RTS has also been made in MOSFETs with metal gate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This low current state has been previously shown to be due to both electron trapping and carrier mobility fluctuation. [12][13][14] In addition, previous research has identified two conditions causing mobility fluctuation through Coulombic scattering, either by a single positively or negatively charged trap. 17 In the presence of either a positive charge only without electron trapping (donor type trap) or a negative charge only due to electron trapping (acceptor type trap), Coulombic scattering will occur.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This low current state has been previously shown to be due to both electron trapping and carrier mobility fluctuation. [12][13][14] In addition, previous research has identified two conditions causing mobility fluctuation through Coulombic scattering, either by a single positively or negatively charged trap. 17 In the presence of either a positive charge only without electron trapping (donor type trap) or a negative charge only due to electron trapping (acceptor type trap), Coulombic scattering will occur.…”
Section: Methodsmentioning
confidence: 99%
“…[7][8][9][10] With the scaling down of metal-oxidesemiconductor field-effect transistors (MOSFETs), random telegraph signal (RTS) have become a major issue that has influenced performance of MOSFETs. [11][12][13][14][15][16][17] The RTS phenomenon is commonly related to the behaviors of a carrier that has been captured and emitted by the oxide trap. Additionally, the operating region of MOSFETs is often chosen in the moderate inversion region due to the need for low power consumption in analog circuits.…”
mentioning
confidence: 99%
“…When devices are scaled down to deep sub-micrometer, the random telegraph signal (RTS) becomes a major issue and influences the performance of MOSFETs. [10][11][12][13] The RTS phenomenon is commonly caused by a carrier that has been captured and emitted by an oxide trap. Although researches on lateral trap position determined by 2-level channel current RTS (2-RTS) have been previously reported, [13][14][15] there are few reports that study the trap position in multilevel RTS.…”
mentioning
confidence: 99%